2007
DOI: 10.1097/yco.0b013e3281938102
|View full text |Cite
|
Sign up to set email alerts
|

Medical comorbidity in bipolar disorder: reprioritizing unmet needs

Abstract: Somatic health issues in individuals with bipolar disorder are ubiquitous, under-recognized and suboptimally treated. Facile screening for risk factors and laboratory abnormalities along with behavioral modification for reducing medical comorbidity are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 100 publications
(110 reference statements)
0
65
0
5
Order By: Relevance
“…31,32 In addition to general medical conditions such as cardiovascular, endocrine, and metabolic diseases, 8,33 patients with BD usually have a wide range of modifiable cardiovascular risk factors such as obesity, smoking, physical inactivity, and poor eating habits. 17 As expected and in line with recent studies from other countries, patients with BD had higher prevalence of the selected cardiovascular risk factors when compared with data regarding the Brazilian population, in which recent studies have shown rates of 5-10% for diabetes and around 30% for hypertension and high cholesterol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 In addition to general medical conditions such as cardiovascular, endocrine, and metabolic diseases, 8,33 patients with BD usually have a wide range of modifiable cardiovascular risk factors such as obesity, smoking, physical inactivity, and poor eating habits. 17 As expected and in line with recent studies from other countries, patients with BD had higher prevalence of the selected cardiovascular risk factors when compared with data regarding the Brazilian population, in which recent studies have shown rates of 5-10% for diabetes and around 30% for hypertension and high cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…1 Patients with BD are subject to premature death from all causes when compared to the general population 2 and usually have several comorbid general medical conditions associated with worse outcomes and higher burden of disease. [3][4][5] Increased rates of obesity, 6,7 diabetes, 8 hypertension, 9 dyslipidemia, 10 and metabolic syndrome [11][12][13] have been reported in recent clinical and epidemiological studies. 14,15 In addition to being exposed to the weight gain effects of the pharmacological treatment, BD patients are more likely to have sedentary lifestyles and poor dietary habits, 16 which are well-established cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Gukokortikoid/insülin sinyal mekanizmaları ve immünoinflamatu-ar efektör İUB ile stres duyarlı genel tıbbi durumlar arasındaki patofizyolojiye işaret eden kesişim noktalarıdır (16). İUB'de değişen beyin enerji metabolizması ve beyin glukoz metabolizmasındaki değişiklikler her iki hastalığın patofizyolojisinde önemli olabilir (17,18).…”
Section: Introductionunclassified
“…Aunque está poco estudiado, los datos disponibles sugieren que diversas enfermedades médicas (cardiovasculares, metabólicas, infecciosas, neurológicas y respiratorias) presentan una prevalencia más elevada en estos pacientes 8,9 . Las razones que contribuyen a esta mayor prevalencia son variadas.…”
Section: Introductionunclassified
“…Sin embargo, hay una tendencia a infradiagnosticar e infratratar las enfermedades médicas entre los pacientes psiquiátricos en general y entre los pacientes bipolares en particular 9,[13][14][15] . De esta situación se deriva la consecuencia de sensibilizar a todos los profesionales de la salud sobre la necesidad de prevenir y tratar adecuadamente las enfermedades físicas en estos pacientes 16 .…”
Section: Introductionunclassified